(untitled) (Jóvenes en la Ciencia, 2025)
Development and analysis of classroom-based teaching exercises aimed at addressing difficulties identified in the reading of complex poetic texts among young groups of high school and college students. Theories and methods from the visual arts, particularly the poetics and work of artist Cy Twombly, were used as a basis for designing the practical sessions. The responses and results of the pilot group’s implementation of the practice were studied from the perspective of multidimensional systemic pedagogy to determine its feasibility and effectiveness in addressing poetic texts at three different levels: recognition of their structure, the plain and underlying meaning of the poems, and understanding of the aesthetic experience resulting from reading poems.